Análisis FINANCIERO Y Administración DE CAPITAL DE TRABAJO A LA COOPERATIVA DE AHORRO Y Crédito “SANTIAGO LTDA,” DE LA PARROQUIA DE SANTIAGO PERIODO 2012 - Tene Macas, Merci Rocio (2015)
The “FINANCIAL ANALYSIS AND WORKING CAPITAL MANAGEMENT " is the theme of this research that develops the same to meet as a prerequisite to choose the degree of Engineer in Public Accounting and Auditing Accountant , objectives geared to get results on the financial position of the entity, in the year of study. Applying Methods of Analysis to Financial Statements of the entity, and financial indicators to establish the actual financial and economic situation of the cooperative; and finally a study of the working capital for current operations, determining where they come from and where will the cash flows and report financial analysis and working capital management, for management of the institution and that so they can make appropriate decisions. The results on Vertical and Horizontal Analysis of Financial Statements of the cooperative is made, the financial indicators and indicators applied beads which were plotted and interpreted; the discussion is determined as a result the financial condition of the cooperative allows knowing the profitability generated which is 0.001 % in relation to its assets, the debt level and 10.17% in terms of liquidity is $ two, % to cover its short-term obligations. The Conclusions and Recommendations were based on the Financial Analysis and Working Capital Management is determined that in 2012 the Cooperative Savings and Credit " SANTIAGO LTDA " maintains its stability and liquidity of debt at a normal level , as well is essential to carry out a reform credit policies in order to give them greater liquidity to the entity.